2014
DOI: 10.2519/jospt.2014.5141
|View full text |Cite
|
Sign up to set email alerts
|

Interrater and Intrarater Reliability of Transverse Abdominal and Lumbar Multifidus Muscle Thickness in Subjects With and Without Low Back Pain

Abstract: Both experienced and trained novice raters provided reliable measurements of TrA and LM thickness in participants with LBP and healthy participants, during rest and contraction. One-time measurements were similar to averaged measurements. Small absolute errors were observed. Public trial registry: Australian New Zealand Clinical Trials Registry ACTRN12613001077752.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 45 publications
6
45
3
Order By: Relevance
“…The USI methods used in this study to assess TrA thickness and AR had acceptable to excellent reliability in all 4 positions assessed for healthy participants. The tabletop reliability for the AR mirrored results from previous studies [10,13,14] with strong reliability, as well as in the seated and standing positions for the TrA. The addition of the walking task and the reliability consistency within that position bolsters the current literature and sets up future studies that could examine TrA activation in a more functional position.…”
Section: Discussionsupporting
confidence: 68%
“…The USI methods used in this study to assess TrA thickness and AR had acceptable to excellent reliability in all 4 positions assessed for healthy participants. The tabletop reliability for the AR mirrored results from previous studies [10,13,14] with strong reliability, as well as in the seated and standing positions for the TrA. The addition of the walking task and the reliability consistency within that position bolsters the current literature and sets up future studies that could examine TrA activation in a more functional position.…”
Section: Discussionsupporting
confidence: 68%
“…Of high‐quality studies, McPherson and Watson (ICC, 0.62–0.93) and Ehsani et al (ICC, 0.63–0.99) reported intra‐rater reliability ICCs that were less than 0.70. The ICCs reported for inter‐rater reliability in high‐quality studies were greater than 0.70 (0.71–1.00), except for Hoppes et al (0.39–0.79). Also, among low‐quality studies, reported ICCs for intra‐ and inter‐rater reliability ranged from 0.26 to 0.99 and 0.68 to 0.97, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Table , the scores of the included studies ranged from 10% to 90%. Also, 16 of 26 reviewed studies (marked a in Table ) obtained a score of 50% or greater and were deemed to be high‐quality articles …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations